PEMBUATAN ARANG AKTIF DARI BIOMAS UNTUK PEMURNI MINYAK KELAPA - Gustan Pari; Hartoyo Hartoyo (Pusat Penelitian dan Pengembangan Hasil Hutan, 1989)
Steam activation char of wood, bamboo, and coconut shell to produce activated charcoal were carried out in a labora- tory scale electric heated retort.The treatment conditions applied for activation were temperature of 700°C, steam flow rate of 30 g/minute and reaction time 15 minutes. The activated charcoals produced from the experiment were respectively used for refining the samples of low grade commercial coconut oil obtained from the market.The results showed that all of the activated charcoal produced can increase the quality of coconut oil to meet requirements of the Indonesian Industrial Standard (Sll).